2008
DOI: 10.4161/chan.2.3.6155
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of caveolin-1-positive domains in the regulation of the acetylcholine receptor's activable pool: Implications in the pathogenesis of a novel congenital myasthenic syndrome

Abstract: Cholesterol modulates the plasmalemma's biophysical properties and influences the function and trafficking of membrane proteins. A fundamental phenomenon that remains obscure is how the plasmalemma's lipid composition regulates the activatable pool of membrane receptors. An outstanding model to study this phenomenon is the nicotinic acetylcholine receptor (nAChR), since the nAChR activatable pool has been estimated to be but a small fraction of the receptors present in the plasmalemma. Studies on the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The partitioning of mutant nAChRs into caveolae that is favored by the introduction of the CBM may contribute to the reduced expression levels observed for the P463W mutant nAChR, as is the case for the Torpedo αC418W mutant nAChR. 46 The increase in nAChR expression levels caused by a tryptophan substitution at position Ser-457 may be due to a favorable californica nAChR δM4 TMD displays a spring motion between its different conformational states, similar to the recently proposed spring model for the αM3 TMD of the Mus musculus nAChR. 24 Helical net diagrams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The partitioning of mutant nAChRs into caveolae that is favored by the introduction of the CBM may contribute to the reduced expression levels observed for the P463W mutant nAChR, as is the case for the Torpedo αC418W mutant nAChR. 46 The increase in nAChR expression levels caused by a tryptophan substitution at position Ser-457 may be due to a favorable californica nAChR δM4 TMD displays a spring motion between its different conformational states, similar to the recently proposed spring model for the αM3 TMD of the Mus musculus nAChR. 24 Helical net diagrams.…”
Section: Discussionmentioning
confidence: 99%
“…the first lipid-exposed mutation that has been shown to produce a Slow Channel Congenital Myasthenic Syndrome (SCCMS) in a patient. 46,54,55 Further studies are underway to determine if the P463W mutant nAChR is cholesterol-sensitive. Taken together, the functional data of the δM4 mutant nAChRs has demonstrated that this TMD plays an important role in the mechanism of channel gating of the Torpedo nAChR.…”
Section: Discussionmentioning
confidence: 99%